NEPENTHES HARAUENSIS, A NEW SPECIES OF NEPENTHACEAE FROM WEST SUMATRA - Hernawati Hernawati; Robi Satria; Ch'ien C. Lee (Research Center for Biology, 2022)
HERNAWATI, SATRIA, R. & LEE, C. C. 2022. Nepenthes harauensis, a new species of Nepenthaceae from West Sumatra. Reinwardtia 21(1): 19‒23. — A new species of Nepenthes (Nepenthaceae) from the Harau region of West Sumatra is described as Nepenthes harauensis Hernawati, R.Satria & Chi.C.Lee. This species shares specific characteristics with both N. bongso and N. singalana but is unique in its thickly coriaceous and petiolate leaves, which are elliptic-oblong and have a distinctly peltate tendril insertion.